8(2y-2)-(9y+5)=

Simple and best practice solution for 8(2y-2)-(9y+5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(2y-2)-(9y+5)= equation:


Simplifying
8(2y + -2) + -1(9y + 5) = 0

Reorder the terms:
8(-2 + 2y) + -1(9y + 5) = 0
(-2 * 8 + 2y * 8) + -1(9y + 5) = 0
(-16 + 16y) + -1(9y + 5) = 0

Reorder the terms:
-16 + 16y + -1(5 + 9y) = 0
-16 + 16y + (5 * -1 + 9y * -1) = 0
-16 + 16y + (-5 + -9y) = 0

Reorder the terms:
-16 + -5 + 16y + -9y = 0

Combine like terms: -16 + -5 = -21
-21 + 16y + -9y = 0

Combine like terms: 16y + -9y = 7y
-21 + 7y = 0

Solving
-21 + 7y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '21' to each side of the equation.
-21 + 21 + 7y = 0 + 21

Combine like terms: -21 + 21 = 0
0 + 7y = 0 + 21
7y = 0 + 21

Combine like terms: 0 + 21 = 21
7y = 21

Divide each side by '7'.
y = 3

Simplifying
y = 3

See similar equations:

| 9/7+1/2(5/6)^2 | | 8x^2/8x^2+16x | | 18x^2+9x-5= | | -x^2-11x+14=0 | | -7+13-6=-5a+6a | | X+2x+2=3x-13 | | -9=3m/4 | | x=49-4(2)(-8) | | 8r-18=-15+7r | | 9x=84+2x | | 5/6-1/36 | | 9w+1/7=5w-3/4+1 | | Y+(-14)=1 | | 0.4(2z+6)0.1=0.5(2z-3) | | a+b-3= | | 2*p/2*p-4 | | -5/9/4/5 | | -12x+12=-13x-1 | | 2(5/2)+1=4 | | 3=0.75b+5-1/4b-4 | | -2-4=3-2x+3x | | (-3+8i)(7+7i)=0 | | 5/2(2.2)+5/2(1.8)+5=15 | | -2(-x+y)=2(-5) | | (x-5)^2/3=25 | | .16d+.6=.25(d+-2) | | sqrt(4x+9)-6x=3 | | 6x-20=-56 | | -3-8c=35 | | .5-7=3 | | 11x+24=180 | | -4w+3+5w=-1+5 |

Equations solver categories